A STUDY OF MANAGEMENT AND CONSERVATION OF WATER RESOURCES AS TODAY’S NEED - Kumar, Gaurav; Arya, Mohan Lal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Water, forests and land together form the earth's ecosystem, in which life is flourishing, nourishing and protecting. Water is not only the main component of the biological ecosystem on earth, but it is also the life force of the earth, the sustainability of growth, sustainability of the environment and synonymous with life on earth. Water is a prerequisite for the continuity of life, livelihood, food, security and development. It is an essential component of the survival of all living beings. From the distant past till today, the story of our development has progressed on the strength of water. All great civilizations have flourished near water sources. Even today, the cultures and livelihoods of human society are based on water, which is rapidly becoming endangered due to the increasing water crisis, because on one hand, due to the monopolistic tendency of man to dominate nature, nature is becoming uncontrolled such as global climate change, which has badly affected the way we live on earth along with the weather. Secondly, due to increasing population and increasing materialism of development, the sustainability of the earth has reduced and in the same proportion water resources are also getting depleted. Hence, at some level humans themselves are responsible for the current situation of increasing water crisis.